ANALISIS PENGARUH PAJAK DAERAH, RETRIBUSI DAERAH, DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PADA PEMERINTAH DAERAH DI JAWA TENGAH TAHUN 2019-2022 - Suhesti Ningsih; Mennik Putriana Syva; Rukmini Rukmini (ITB AAS INDONESIA, 2023)
The study aims to determine The effect of local Taxes on the finansial performance of district/city regional goverment financial in Central Jawa in 2019-2022, The effect of Regional Retribution on Regional Goverment Finansial Performance in 2019-2022, The effect of Capital Expenditure on Regional Goverment Finansial Performance in 2019-2022. This Research is a quantitative reserch. The subject of this research is the District/City Regional Goverments in Ceintral Jawa, totaling 35 regencies and cities. The data used comes from the Realization Report of the Directorate General of Taxes, Ministry of Finance. Data collection techniques using the documentation method. The requirements analysis test uses the classical assumption test, namely the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing in this study uses multiple linear regression analysis, F test, t test, and coefficient of determination test (R2). The results of the study show that Regional taxes have a sigmificant positive effect on the Finansial Performance of District/City Goverments in Central Jawa in 2019-2022, Regional Levies have no significant efeect on the Finansial Performance of Regency/City Goverments in Central Java in 2019-2022, Capital Expenditure has a significant negative effect on the Financial Performance of Regency/City Regional Goverments in Central Java in 2019-2022.